Rare kaon decays - Ceccucci, Augusto; Lazzeroni, Cristina (Comptes Rendus. Physique, 2020)
The article reviews the status of rare K decay physics. The explored area covers a broad program, ranging from precise tests of flavour theory and CP-violation to the searches for explicit violations of the standard model and the study of strong interactions at low energies.